The Karamanli Text of Teodosiy of Sinai’s "A book for learning of three languages". Language and Cultural Problems - Saldžiev, Hristo (Zeitschrift für Balkanologie, 2009)
The article deals with the Karamanli (Turkish) part of a tri-lingual Bulgarian-Greek-Turkish book issued in 1841 by the print house of the Bulgarian monk Theodosiy of Sinai. On the basis of methodology of classical historical investigations and structural linguistics and anthropology several kinds of problems are taken into consideration: the evidence of Karamanlies in the 19th-century Bulgarian sources; the exact number of translators; the phonetic, morphologic and syntax peculiarities of Karamanli text; and its religious and kinship terminology. The final conclusion is that in spite of the designation “Karamanli” the language of text bears the typical characteristics of the Turkish Balkan dialects and is a mix between East and West Rumelian Turkish vernaculars. The religious terminology consists of Muslim terms used for expression of Christian notions and Greek loan words – some of them obviously taken from the folk Christianity. The kinship terminology shows the peculiarities of a town community influenced by both, Christian and Muslim normative systems.